2010
DOI: 10.1111/j.1365-3091.2009.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and facies heterogeneities of shallow carbonate ramp cycles (Sinemurian, Lower Jurassic, North-east Spain)

Abstract: The lateral continuity and facies heterogeneities of metre-scale cycles in a greenhouse Lower Jurassic (Sinemurian) carbonate ramp from the northern Iberian Basin (Spain) was evaluated from extensive field analysis carried out on a well-exposed 12 km long outcrop. Eleven high-frequency continuous cycles and their bounding surfaces are traceable laterally through the entire outcrop. However, three of these cycles are found to split laterally into discontinuous cycles of more limited distribution (up to 3 to 5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 37 publications
2
19
0
5
Order By: Relevance
“…The finning up-ward facies indicate that these lags probably correspond to washover expanding into the protected lagoon and intertidal set-tings (cf. Bádenas et al, 2010). Moreover, during the storms, shell debris of marine organisms would be transported and washed from the shallow subtidal to the intertidal-lower supratidal environments.…”
Section: Shallow Subtidal Cycles (Type A)mentioning
confidence: 99%
See 1 more Smart Citation
“…The finning up-ward facies indicate that these lags probably correspond to washover expanding into the protected lagoon and intertidal set-tings (cf. Bádenas et al, 2010). Moreover, during the storms, shell debris of marine organisms would be transported and washed from the shallow subtidal to the intertidal-lower supratidal environments.…”
Section: Shallow Subtidal Cycles (Type A)mentioning
confidence: 99%
“…Adams and Grotzinger, 1996) even though a local subsidence can not rule out (Hamon and Merzeraud, 2008). As Bádenas et al (2010) suggest, the lateral continuity of cycles can be controlled by depositional topography or by local subsi-dence, where facies distribution results from production rate and accumulation. Evidence of sea level fall was reported by Palma et al(2010Palma et al( , 2011 because of the presence of paleokarstic breccias facies.…”
Section: Fischer Plot Analysismentioning
confidence: 99%
“…Many workers have described laterally persistent platform cycles (Demicco, 1985;Goldhammer et al, 1987;Goldhammer, Dunn, & Hardie, 1990;Goodwin & Anderson, 1985;Grotzinger, 1986;Koerschner & Read, 1989;Osleger & Read, 1991), although lithofacies within individual cycles can vary laterally (Adams & Grotzinger, 1996;Bádenas, Aurell, & Bosence, 2010;Cloyd, Demicco, & Spencer, 1990;Cowan & James, 1996;Egenhoff, Peterhänsel, Bechstädt, Zühlke, & Grötsch, 1999;Laporte, 1967;Obermaier, Ritzmann, & Aigner, 2015;Pratt & James, 1986;Samankassou, Strasser, Di Gioia, Rauber, & Dupraz, 2003). Lateral facies variations have also been reported from modern sites (Bosence, 2008;Eberli, 2013;Enos & Perkins, 1979;Harris, Purkis, & Ellis, 2011;Purkis & Harris, 2016;Wilkinson & Drummond, 2004) and from the Triassic Dachstein platform in the Northern Calcareous Alps (Enos & Samankassou, 2002;Piller, 1976Piller, , 1981Satterley, 1996b;Zankl, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore the combination of autogenic/autocyclic and allogenic/allocyclic processes that is responsible for sediment deposition and the formation of the final sedimentary record. Many case studies have already shown and discussed the coexistence of autocyclic and allocyclic processes, for example: Sami and James (1994) in the Proterozoic of northwest Canada; Jiang et al (2003) in the Proterozoic of the Lesser Himalaya; Adams and Grotzinger (1996) in the Middle Cambrian of California; Cowan and James (1993) in the Late Cambrian of Newfoundland; Smith and Read (2001) in the Mississippian of Illinois; Yang et al (1998) in the Late Pennsylvanian and Early Permian of Texas; Bádenas et al (2010) in the Sinemurian of Spain; Carpentier et al (2010) in the Oxfordian of France; Sattler et al (2005) in the Barremian and Aptian of Oman; Lehmann et al (1998) in the Barremian to Albian of northeastern Mexico; Rankey (2002) in the Holocene of the Bahamas.…”
Section: Autocyclic Processesmentioning
confidence: 99%